Characterization of Cas proteins for CRISPR‐Cas editing in streptomycetes. Issue 9 (30th May 2019) - Yeo, Wan Lin; Heng, Elena; Tan, Lee Ling; Lim, Yi Wee; Lim, Yee Hwee; Hoon, Shawn; Zhao, Huimin; Zhang, Mingzi M.; Wong, Fong Tian
Abstract: Application of the well‐characterized Streptococcus pyogenes CRISPR‐Cas9 system in actinomycetes streptomycetes has enabled high‐efficiency multiplex genome editing and CRISPRi‐mediated transcriptional regulation in these prolific bioactive metabolite producers. Nonetheless, SpCas9 has its limitations and can be ineffective depending on the strains and target sites. Here, we built and tested alternative CRISPR‐Cas constructs based on the standalone pCRISPomyces‐2 editing plasmid. We showed that Streptococcus thermophilus CRISPR1 Cas9 (sth1Cas9), Staphylococcus aureus Cas9 (saCas9), and Francisella tularensis subsp. novicida U112 Cpf1 (fnCpf1) are functional in multiple streptomycetes, enabling efficient homology‐directed repair‐mediated knock‐in and deletion. In strains where spCas9 was nonfunctional, these alternative Cas systems enabled precise genomic modifications within biosynthetic gene clusters for the discovery, production, and diversification of natural products. These additional Cas proteins provide us with the versatility to overcome the limitations of individual CRISPR‐Cas systems for genome editing and transcriptional regulation of these industrially important bacteria. Abstract : Application of the well‐characterized Streptococcus pyogenes CRISPR‐Cas9 (spCas9) system in streptomycetes has enabled high‐efficiency multiplex genome editing and CRISPRi‐mediated transcriptional regulation in these prolific natural product producers. Nonetheless, spCas9 can be ineffective depending on strains and target sites. To overcome some of these limitations, we characterized Streptococcus thermophilus CRISPR1 Cas9 (sth1Cas9), Staphylococcus aureus Cas9 (saCas9), and Francisella tularensis subsp. Novicida U112 Cpf1 (fnCpf1) and successfully expanded the Cas protein toolbox for genome editing in these industrially important streptomycetes.